Imaging magnetic and ferroelectric domains and interfacial spins in magnetoelectric La0.7Sr0.3MnO3/PbZr0.2Ti0.8O3 heterostructures. (27th November 2015) - Huang, C-Y; Zhou, J; Tra, V T; White, R; Trappen, R; N'Diaye, A T; Spencer, M; Frye, C; Cabrera, G B; Nguyen, V; LeBeau, J M; Chu, Y-H; et al.
Abstract: Strong magnetoelectric coupling can occur at the interface between ferromagnetic and ferroelectric films. Similar to work on interfacial exchange bias, photoemission electron microscopy was utilized to image both magnetic and ferroelectric domains and the resulting interfacial Ti spin in the same locations of La0.7 Sr0.3 MnO3 /PbZr0.2 Ti0.8 O3 heterostructures. Multiple image analysis techniques, which could be applicable for a variety of fields needing quantitative data on image switching, confirm both improved magnetic switching and an increased population of interfacial spins with increased thickness of the ultrathin La0.7 Sr0.3 MnO3 layer. The perpendicular orientation of the interfacial spins is also discussed. This work suggests a magnetoelectric dead layer, with reduced interfacial magnetoelectricity when thin magnetic films are present.